2004
DOI: 10.1158/0008-5472.can-03-1185
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chicken Ovalbumin Upstream Promoter-Transcription Factor II Enhances Invasiveness of Human Lung Carcinoma Cells

Abstract: Chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII) plays an essential role in angiogenesis and development. It is differentially expressed in tumor cell lines, but its role in carcinogenesis is largely unknown. We demonstrate here that noninvasive human lung cancer cells become invasive when COUP-TFII was expressed. The expression of extracellular matrix degrading proteinases, such as matrix metalloproteinase 2 and urokinase-type plasminogen activator, was upregulated in these cells. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
(42 reference statements)
3
34
1
Order By: Relevance
“…Reprobing with Src-specific antibody confirmed that the 60-kDa band represented the phosphorylated pp60 c-Src protein. To investigate the functional relationship between Src and Id1 and its therapeutic implications, we examined a panel of human cancer cell lines from four types of cancer, including lung (A549 and H460), breast (T47D and MDA-MB231), prostate (LNCaP and PC-3), and colon (HCT-116 and HT-29), each represented by a pair of cell lines with different invasive potential (36)(37)(38)(39). Protein extracts of cells grown under normal conditions were subjected to Western blotting for pY419-Src, total Src, Id1, and actin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reprobing with Src-specific antibody confirmed that the 60-kDa band represented the phosphorylated pp60 c-Src protein. To investigate the functional relationship between Src and Id1 and its therapeutic implications, we examined a panel of human cancer cell lines from four types of cancer, including lung (A549 and H460), breast (T47D and MDA-MB231), prostate (LNCaP and PC-3), and colon (HCT-116 and HT-29), each represented by a pair of cell lines with different invasive potential (36)(37)(38)(39). Protein extracts of cells grown under normal conditions were subjected to Western blotting for pY419-Src, total Src, Id1, and actin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CXCL12 expression in primary tumors has recently been reported to drive breast cancer metastasis (Ray et al 2015). The other COUP-TF member, COUP-TF2, may also have a role in breast cancer cell migration and invasion with a report that transfection of COUP-TF2 into MDA-MB-231 resulted in increased migration and invasion of these cells (Navab et al 2004). Together these findings suggest a potential involvement of COUP-TFs in epithelialto-mesenchymal transition and migration of breast cancer cells.…”
Section: Estrogen-relatedmentioning
confidence: 92%
“…Expression of COUP-TFII in human lung carcinoma cell lines was reported to increase invasive and migratory abilities (39). To examine whether COUP-TFII expression correlates with the invasiveness of human breast cancer cells, we examined in vitro cell invasiveness and migration in vector-transfected versus the LY2-COUP-TFII cell line.…”
Section: Cancer Researchmentioning
confidence: 99%